Role of Bloodstain Pattern Analysis in the Reconstruction of Crime Scene - Naorem, Prerna; Kumar, Aditya (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Bloodstain pattern analysis or BPA is the analysis of the size, shape and distribution of bloodstains in crime scene which not just focuses on finding the angle and direction of bloodstain but also extent to the detection of the blood to the DNA profiling which aids in the reconstruction of events. There is certain method used in BPA ranging from traditional method such as the use of trigonometric calculation and stringing method to advanced software such as HemoSpat, HemoVision, etc. Even though there has been a vast improvement in BPA, it is still not without any challenges such as the risk of contamination, the variability of blood behaviour in various environmental circumstances and lastly human errors. While the reliability of BPA has been strengthened with the recent improvement in technologies, in order to improve its accuracy, legality and application in forensic investigations, more study and standards are required.